Opbouwwerk en werkgelegenheid : studiekonferentie 29 en 30 januari 1981 - Mayo, Marjorie; Craig, Gary; Sharman, Nick ('s-Hertogenbosch: NIMO, 1981)
"Inleiders: Marjorie Mayo, Gary Craig, Nick Sharman, ... et al."